A light in the darkness: Early phases of development and the emergence of cognition - Elisa Cainelli; Giulia Stramucci; Patrizia Bisiacchi (Developmental Cognitive Neuroscience)
During the prenatal period, the major brain development milestones are posed and calibrated through different mechanisms, among which endogenous activity, that prepares the ''system'' to face the external environment. However, the specific nature of the human nervous system, intended for brain plasticity that is varied by brain area and prolonged over time, requires much time for environmental experiences to shape the cerebral circuitries. Therefore, the neonate completely depends on the caregiver, and during the first months of postnatal life, it exhibits a transitory and limited repertoire of behaviors and skills that favors the mother in her new role. This transitory condition will gradually give way to more mature competencies, the milestones of which are posed within 2 years of age. This review takes a new perspective on early development and attempts to trace the remarkable changes from in-utero period to the second year of postnatal life, posing a bridge between the neurobiological substrate and behavioral development. We based our work on the ''normal'' development, pointing out the risks inherent in any development process.